The rocking spectrum and the limitations of practical design methodologies. - Makris, Nicos (Earthquake engineering & structural dynamics.)
This paper is concerned with the superficial similarities and fundamental differences between the oscillatory response of a single degree of freedom (SDOF) oscillator (regular pendulum) and the rocking response of a slender rigid block (inverted pendulum). The study examines the distinct characteristics of the rocking spectrum and compares the observed trends with those of the response spectrum. It is shown that the rocking spectrum reflects the kinematic characteristics of the ground motions that are not identifiable by the response spectrum. The paper investigates systematically the fundamental differences in the dynamical structure of the two systems of interest and concludes that rocking structures cannot be replaced by 'equivalent' SDOF oscillators. The study proceeds by examining the validity of a simple, approximate design methodology, initially proposed in the late 1970s and now recommended in design guidelines to compute rotations of slender structures by performing iteration either on the true displacement response spectrum or design spectrum. This paper shows that the simple design approach is inherently flawed and should be abandoned, in particular for smaller, less slender blocks. The study concludes that the exact rocking spectrum emerges as a distinct intensity measure of ground motions.